Okul öncesı̇ öğretmen ve öğretmen adaylarının yer temellı̇ eğı̇tı̇m yaklaşımına yönelı̇k görüşlerı̇nı̇n değerlendı̇rı̇lmesı̇ (Çanakkale ı̇lı̇ örneğı̇) - İkiz, Şirin (My University, 2022)
Yer Temelli Eğitim (YTE); öğrenme ve öğrenmenin bir başlangıç noktası, yerel toplum ve çevreyi kullanma süreci, öğrencilerin, öğretmenlerin ve toplumdaki yetişkinlerin yaşadıkları doğal, toplumsal ve kültürel çevrede edinilen, bilgi ve beceri kazanmayı sağlayan bir eğitim yaklaşımı olarak tanımlamaktadır. Yer temelli eğitim bireyin akademik performansını geliştirme, öğrenci ve öğretmen arasındaki olumlu ilişkiler oluşması, öğrenci motivasyonunun artması, devamsızlık sorununun azalması, davranış problemlerinde azalma ve toplumla daha çok vakit geçirme isteği, sosyalleşmenin artması, fiziksel, bedensel ve zihinsel sağlık, eğlenerek öğrenme ve doğayı keşfetme gibi yararlar sağlamaktadır. Bu araştırmanın genel amacı; okul öncesi öğretmenlerinin ve öğretmen adaylarının yer temelli eğitim yaklaşımına ilişkin görüşlerini değerlendirmektir. Okul öncesi öğretmenlerinin Yer Temelli Eğitim Yaklaşımına ilişkin görüşleri; çalıştıkları ilçeye, cinsiyetlerine, öğrenim düzeylerine, çalıştıkları kurumdaki görev türüne, meslekteki hizmet sürelerine, çevre eğitimi ile ilgili hizmet içi eğitim alıp almadıklarına, öğretmen adaylarının Yer Temelli Eğitim Yaklaşımına ilişkin görüşleri, cinsiyetlerine, öğrenim düzeylerine çevre eğitimi ve okul dışı öğrenme ortamları ile ilgili hizmet içi eğitim alıp almadıklarına göre anlamlı farklılıklar göstermekte midir? sorularına yanıt bulmak amaçlanmaktadır. Araştırma betimsel bir araştırmadır. Okul öncesi öğretmen ve öğretmen adaylarının Yer Temelli Eğitim Yaklaşımına ilişkin görüşlerini değerlendirmek için araştırmacı tarafından alan yazın incelendikten sonra hazırlanan ve likert tipi sorulardan oluşan “Yer Temelli Eğitim Yaklaşımı Değerlendirme Formu” uygulanmıştır. Araştırmanın evrenini, Çanakkale il merkezi ve ilçe merkezlerinde görev yapan 170 okul öncesi öğretmeni ve Çanakkale 18 Mart Üniversitesi Okul Öncesi Öğretmenliği 1. 2. 3 ve 4. sınıfta okuyan 188 okul öncesi öğretmen adayları oluşturmaktadır. Araştırma sonucunda öğretmenlerin ve öğretmen adaylarının yer temelli eğitim yaklaşımına olumlu baktıkları ve etkili bir yaklaşım olduğunu düşündükleri görülmektedir. Öğretmenlerin yer temelli eğitim yaklaşımının bilgi ve beceri kazandırma, doğa ve toplum bilinci oluşturma, doğal, kültürel ve toplumsal sorumluluk bilincini geliştirme boyutlarına cinsiyet farkı olmaksızın katıldıkları görülmektedir. iv Yer bağlılığı oluşturma boyutunda ise, kadın katılımcılar yer temelli eğitimin yer bağlılığını desteklediği konusunda görüş belirtirken, erkek katılımcıların az etkili olduğunu düşündükleri görülmektedir. Bilgi ve beceri kazandırma, doğa ve toplum bilinci oluşturma, doğal, kültürel ve toplumsal sorumluluk bilincini geliştirme ve yer bağlılığı oluşturma alt boyutlarına eğitim düzeyi, kıdem düzeyi, görev türü ve çevre eğitimi konulu hizmet içi eğitim alma durumu farkı olmaksızın katıldıkları görülmektedir. Öğretmenlerin yer temelli eğitim yaklaşımının bilgi ve beceri kazandırma boyutu ve doğa ve toplum bilinci oluşturma boyutuna ilişkin görüşleri, Merkez ilçe, Ayvacık, Biga gibi ilçelerden görüşler daha etkili olduğuna inanma yönündeyken, diğer ilçelerde görev yapanların görüşleri farklılaşmaktadır. Öğretmenlerin yer temelli eğitim yaklaşımının yer bağlılığı oluşturma ve doğal, kültürel ve toplumsal sorumluluk bilincini geliştirme alt boyutlarına ilçe düzeyi farkı olmaksızın katıldıkları görülmektedir. Araştırma sonucunda öğretmen adaylarının yer temelli eğitim yaklaşımının, doğa ve toplum bilinci oluşturma, yer bağlılığı oluşturma ve doğal, kültürel ve toplumsal sorumluluk bilincini geliştirme alt boyutlarına cinsiyet farkı olmaksızın katıldıkları görülmektedir. Bilgi ve beceri kazandırma alt boyutunda cinsiyet değişkenine göre anlamlı bir farklılaşma saptanmıştır. Kadın öğretmen adaylarının yer temelli eğitim yaklaşımın bilgi ve beceri kazandırma boyutuna ilişkin görüşleri daha fazla olumlu yöndeyken, erkek adayların daha az etkili olduğunu düşündükleri görülmektedir. Öğretmen adaylarının yer temelli eğitim yaklaşımının, doğa ve toplum bilinci oluşturma, yer bağlılığı oluşturma ve doğal, kültürel ve toplumsal sorumluluk bilincini geliştirme alt boyutlarına sınıf düzeyleri farkı olmaksızın katıldıkları görülmektedir. Öğretmen adaylarının yer temelli eğitimin, bilgi ve beceri kazandırma konusunda yeterli olduğuna ilişkin düşünceleri 2. ve 4. sınıflarda olumlu iken diğer sınıf düzeylerine göre farklılaştığı görülmektedir. Çevre eğitimi almış öğretmen adaylarının yer temelli eğitim yaklaşımının bilgi ve beceri kazandırma boyutuna ve doğal, kültürel ve toplumsal sorumluluk bilinci ilişkin görüşleri daha az olumlu yöndeyken, almamış adayların daha çok etkili olduğunu düşündükleri görülmektedir. Yer temelli eğitim yaklaşımın doğa ve toplum bilinci kazandırma ve yer bağlılığı oluşturma boyutlarına ilişkin görüşleri daha çok olumlu yöndeyken, almamış adayların daha az etkili olduğunu düşünmekte olduğu sonucu çıkmaktadır. v Çevre eğitimi dersini zorunlu ya da seçmeli almış olma durumu fark etmeksizin okul öncesi öğretmen adaylarının yer temelli eğitim yaklaşımın bilgi ve beceri kazandırma, doğal, kültürel ve toplumsal sorumluluk bilinci, doğa ve toplum bilinci kazandırma ve yer bağlılığı boyutlarına ilişkin görüşlerinin olumlu yönde olduğu görülmektedir. Öğretmen adaylarının; bilgi ve beceri kazandırma, doğa ve toplum bilinci oluşturma, yer bağlılığı oluşturma ve doğal, kültürel ve toplumsal sorumluluk bilincini geliştirme alt boyutlarına ilişkin görüşlerinin okul dışı öğrenme dersini almış olma durumu fark etmeksizin çoğunluğunun olumlu yönde olduğu görülmektedir. Yer Temelli Eğitim Yaklaşımı ile ilgili yurtdışında yapılan çalışmalar incelendiğinde; YTEY dünyada aktif olarak kullanılan ve araştırılan bir eğitim yaklaşımıdır. Yer Temelli Eğitim yaklaşımı ile ilgili ülkemizde yapılan çalışmalar incelendiğinde, çalışmaların yeterli olmadığı görülürken, okul öncesinde yapılan çalışmaların henüz olmadığı görülmektedir. YTE yaklaşımına yönelik uygulamalı çalışmaların çoğalması ile eğitimcilerin bu konuya dikkatlerini çekerek, YTE yaklaşımına yönelik etkinliklere daha çok yer verilmesi sağlanabilir.

Place-based education (PBE) is defined as a starting point of learning and learning, the process of using the local community and environment, a teaching approach that enables students, teachers and adults in the community to acquire knowledge and skills in the natural, social and cultural environment in which they live. Place-based education can improve the individual's academic performance, the formation of positive relationships between teacher and student, increasing student motivation, the problem of absenteeism reduction, a reduction in behavior problems and a request to spend more time with the community, increase socialization, physical, and mental and physical health, fun, learning and discovering nature, such as benefits. The overall aim of this research is to evaluate the views of preschool teachers and prospective teachers on the approach of place-based education. With the research to be carried out in line with this general aim, do the views of preschool teachers regarding the place-based education approach differ significantly according to the district they work in, their gender, their level of education, their type of job in the institution they work in, their length of service in the profession, whether they received in-service training on environmental education and out-of-school learning environments? Are there any significant differences in teacher candidates ' views on the approach of Place-Based Education based on their gender, level of education whether they received in-service training on environmental education and out-of-school learning environments? It is intended to find answers to their questions. Research is descriptive research. In the study, which is one of the descriptive approach to ‘scan’ the model will be used, and pre-school teachers and teacher candidates place-based education approach prepared by the researcher after examining to assess their opinions regarding the field type and Likert-type questions consisting of “Place-based education approach evaluation form” was applied. The universe of the research consists of pre-school teachers and pre-school teacher candidates who work in Çanakkale city center and district centers. A sample of the study included 170 pre-school teachers who served in the 2021-2022 academic year and Çanakkale 18 Mart University Preschool Education 188 teacher candidates studying in 1st, 2nd, 3rd and 4th grades Pre-School Teachers 1. 2. 3 and 4 of Çanakkale March 18 University. vii As a result of the research, it is seen that teachers and teacher candidates have a positive view of place-based education approach and think that it is an effective approach. It is seen that teachers participate in the dimensions of place-based education approach to gain knowledge and skills, to create awareness of nature and society, and to develop awareness of natural, cultural and social responsibility, regardless of gender. In the dimension of creating place attachment, it is seen that while female participants express an opinion that place-based education supports place attachment, male participants think that it is less effective. It is seen that they participate in the sub-dimensions of acquiring knowledge and skills, raising awareness of nature and society, developing awareness of natural, cultural and social responsibility, and creating place attachment, regardless of their education level, seniority level, job type and in-service training on environmental education. While the opinions of the teachers on the dimension of acquiring knowledge and skills and the dimension of creating nature and community awareness of the place-based education approach, the opinions of the districts such as Merkez, Ayvacık and Biga are in the direction of believing that it is more effective, the opinions of those working in other districts differ. It is seen that teachers participate in the sub-dimensions of creating place attachment and developing natural, cultural and social responsibility awareness of place-based education approach, regardless of district level. As a result of the research, it is seen that teacher candidates participate in the sub-dimensions of place-based education approach, creating awareness of nature and society, creating place attachment and developing awareness of natural, cultural and social responsibility, regardless of gender. A significant difference was found in the sub-dimension of acquiring knowledge and skills according to the gender variable. While the opinions of female teacher candidates about the dimension of gaining knowledge and skills of place-based education approach are more positive, it is seen that male teacher candidates think that it is less effective. It is seen that teacher candidates participate in the sub-dimensions of place-based education approach, creating nature and community awareness, creating place attachment and developing natural, cultural and social responsibility awareness, regardless of their class levels. While the teacher candidates' thoughts on the ability of place-based education to gain knowledge and skills were positive in the 2nd and 4th grades, it was seen that they differed according to other grade levels. viii While the opinions of the teacher candidates who received environmental education about the knowledge and skill acquisition dimension of the place-based education approach and the awareness of natural, cultural and social responsibility are less positive, it is seen that the candidates who have not received it think that it is more effective. It is concluded that while the views of place-based education approach on the dimensions of raising awareness of nature and society and creating place attachment are more positive, the candidates who have not taken it think that it is less effective. It is seen that the majority of the teacher candidates' views on the sub-dimensions of acquiring knowledge and skills, raising awareness of nature and society, creating place attachment and developing the awareness of natural, cultural and social responsibility are positive, regardless of whether they have taken the out-of-school learning course. When the studies conducted abroad on the Place-Based Education Approach are examined; PBEA is an educational approach that is actively used and researched in the world. When the studies conducted in our country on the Place-Based Education approach are examined, it is seen that the studies are not sufficient, but there are no studies conducted in pre-school yet. With the increase of applied studies on the PBE approach, it can be ensured that the activities related to the PBE approach are emphasized by drawing the attention of the educators to this issue.
Evaluation of the pre-school teacher and teacher candidates' opinions on the place based education approach (case of Çanakkale)
Keywords: 21. yy. becerileri; Okul öncesi eğitim; Okul öncesi öğretim; Okul öncesi öğretmenleri; Partnership for 21st Century Learning; Place-based education; Pre-school education; Preschool teachers; Preschool teaching; Yer temelli eğitim